PENGETAHUAN IBU DAN KEBIASAAN MENGGOSOK GIGI ANAK BERHUBUNGAN DENGAN KEJADIAN KARIES GIGI PADA ANAK - Indanah Indanah; Umi Faridah; Siti Mutomimah (Universitas Muhammadiyah Kudus, 2024)
The most common dental problem in children is dental caries. Dental caries is tooth decay that occurs in the hard tissues of the teeth, namely in tooth enamel, joint teeth and gums. Lack of maternal knowledge and improper brushing habits performed in children are associated with the incidence of dental caries in children. This study aims to determine the relationship between maternal knowledge and tooth brushing habits in children with the incidence of dental caries in children.This study was conducted on school-age children in one of the elementary schools in Jati sub-district, Kudus Regency. The samples used in this study were 144 children with a sampling method in the form of a purposive method. Data collection is carried out using questionnaires that have been tested for validity and reliability.The results showed that there was a significant relationship between maternal knowledge and tooth brushing habits in children with the incidence of dental caries (p value 0.05). Mothers with less knowledge had 147 times the risk of children with dental caries (OR: 147.4) and children with poor brushing habits were 805 times more likely to develop dental caries (OR; 805)Conclusion: There is a significant relationship between maternal knowledge and the child's toothbrushing habits with the incidence of dental caries in children.